Relationship between clinical outcomes measures and personal and social performance functioning in a prospective, interventional study in schizophrenia. Issue 2 (23rd December 2020) - Vauth, Roland; Carpiniello, Bernardo; Turczyński, Jacek; Ivanov, Mikhail; Cherubin, Pierre; Lahaye, Marjolein; Schreiner, Andreas
Abstract: Objectives: To explore clinical and demographic characteristics impacting patient functioning by determining extent of overlap in factors driving change in Personal and Social Performance (PSP) and other clinical outcomes. Methods: Post‐hoc analysis from a single‐arm trial of paliperidone extended release in adult patients with nonacute symptomatic schizophrenia. Psychosocial functioning measures: PSP, Clinical Global Impression–Severity (CGI‐S), Positive and Negative Syndrome Scale (PANSS), Short‐Form 36 (SF‐36), treatment satisfaction, sleep quality/daytime drowsiness, and Extrapyramidal Symptoms Rating Scale. Results: Highest correlations with PSP total score change included PANSS total score change (Spearman's r = 0.607), PANSS general psychopathology change ( r = 0.579), and CGI‐S change ( r = 0.569). A PSP score change of −32 predicted 90% probability of deterioration in CGI‐S (score change of ≥1). The power of PSP change to predict PANSS total score change was lower. Linear stepwise regression demonstrated independent relationships for PSP change and: PANSS total change; CGI‐S change; SF‐36 Mental Component change; treatment satisfaction at endpoint; PSP at baseline; previous psychiatric hospitalizations. R 2 = 0.55 meant that 45% of PSP variation could not be explained by other clinical outcome measures. Conclusions: Psychosocial functioning improvement is important in schizophrenia. PSP may be valuable for assessing functioning; it encompasses psychosocial and clinical factors not measured by other established assessments.